The Effect of Corporate Governance Policies and Practices on the Financial Performance of Companies in the Financial Times Stock Exchange 100 - Nkiru Patricia Chude; Olufemi Yeye; Daniel Izuchukwu Chude; Ikeora, J.J.E (Cigarskruie: Journal of Educational and Islamic Research, 2025)
This study analyzes how corporate governance influences the profitability of FTSE 100 firms in the United Kingdom. Specifically, the study examines the effects of board size, CEO duality, board diversity, and board independence on the return on assets (ROA) of FTSE 100 companies listed on the London Stock Exchange. The research adopts a quantitative design with a positivist worldview. Panel data were drawn from the annual financial statements of FTSE 100 firms listed on the London Stock Exchange for the year 2021, with a study period spanning 2011–2021. Data analysis was conducted using Ordinary Least Squares (OLS) techniques. Results indicate that board size has a negative effect on ROA, while CEO duality has a significantly positive effect on ROA. Additionally, board diversity has a significantly positive effect on ROA, whereas board independence has a positive but non-significant effect on the ROA of FTSE 100 firms in the UK. Based on these findings, the study recommends: (i) appointing qualified candidates to the board based on their credentials; (ii) given the global push for greater female boardroom participation, measures should be implemented to increase the percentage of women on company boards; (iii) increasing the number of independent directors on the board, considering their credentials, expertise, capabilities, and experience to perform their duties; (iv) ensuring that the chair of the board and the CEO remain independent to enhance oversight and improve firm performance.